A colecção de antiguidades egípcias do Museu de História Natural da Universidade do Porto - Cunha, Maria José; Sousa, Rogério Ferreira de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In addition to providing a brief historical and archaeological characterisation of the Egyptian collection conserved at the Porto University Museum of Natural History, this article also seeks to explain the origin of this collection and trace its path within the very University.